Marketing Strategy of Wardah's Digital Da'wah Management - Asni Leliana; Muhammad Zen (Sahabat Publikasi, 2023)
Being beautiful and youthful is the dream of all women. Cosmetics are generally materials that are polished, sprayed or rubbed into the body creating freshness, smoothness, softness, purity and fragrance for the wearer. No wonder, several cosmetic industries compete for it such as beauty products. The goal is for women to look beautiful as users of the product. The use of cosmetics at an early age or side effects can also occur with short- or long-term use. The negative effects caused are usually triggered by several chemicals that are specifically used as mixed ingredients in cosmetics. Cosmetics that follow their products specifically in an Islamic way are Wardah Cosmetics produced by PT Pusaka Tradition Ibu (PTI). Currently, the development of industries, especially in Indonesia, such as cosmetic products is growing very rapidly. The idea of the initial stage of this research is to determine First, the objects observed and examined as well as the observations made on observable objects that are predetermined, the commitment of identifying potential problems of observable objects. The sampling technique used in this study is an expert sample is an example of sample expediency included in the non-probability category. The results of this study get several points to be followed up in order to get solutions in completing the strategy as well as marketing changes in wardah cosmetic products and Da'wah Management's views on the strategy. These points are the Analysis of the Final Results of Wardah's Cosmetic Marketing Strategy and Customer Desires in buying wardah cosmetic products.